Microsatellite analysis of the GLC1B locus on chromosome 2 points to NCK2 as a new candidate gene for normal tension glaucoma. Issue 9 (22nd August 2008) - Akiyama, M; Yatsu, K; Ota, M; Katsuyama, Y; Kashiwagi, K; Mabuchi, F; Iijima, H; Kawase, K; Yamamoto, T; Nakamura, M; Negi, A; Sagara, T; et al.
Abstract : Aims: The aim of this study was to investigate the association between normal tension glaucoma and the candidate disease locus glaucoma 1, open angle, B (GLC1B) on chromosome 2. There are many reports describing the results of association or linkage studies for primary open angle glaucoma (POAG), with GLC1B as one of the loci associated with normal or moderately elevated intraocular pressure. However, there are few reports about the association of genes or defined genomic regions with normal tension glaucoma, which is the leading type of glaucoma in Japan. The GLC1B locus is hypothesized to be a causative region for normal tension glaucoma. Methods: Genomic DNA was extracted from whole blood of normal tension glaucoma (n = 143) and healthy controls (n = 103) of Japanese origin. Results: Fifteen microsatellite markers within and/or near to the GLC1B locus were genotyped, and their association with normal tension glaucoma was analysed. Two markers D2S2264 and D2S176 had significant positive associations. Conclusion: The D2S176 marker had the strongest significant association and it is located 24 kb from the nearest gene NCK2, which now becomes an important new candidate gene for future studies of its association with normal tension glaucoma.